2019
DOI: 10.1111/bjd.18384
|View full text |Cite
|
Sign up to set email alerts
|

A 24‐week multicentre, randomized, open‐label, parallel‐group study comparing the efficacy and safety of ixekizumab vs. fumaric acid esters and methotrexate in patients with moderate‐to‐severe plaque psoriasis naive to systemic treatment

Abstract: Summary Background Interleukin‐17 antagonists have received a first‐line label for moderate‐to‐severe plaque psoriasis. Objectives We conducted the first head‐to‐head trial between the two most commonly used first‐line therapies in Germany, fumaric acid esters (FAEs) and methotrexate, and the interleukin‐17A antagonist, ixekizumab. Methods Systemic‐naive patients were randomized in this parallel‐group, active‐comparator, open‐label, rater‐blinded trial (each group n = 54). The primary outcome was the proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 21 publications
6
38
0
Order By: Relevance
“…The trials all had similar designs (randomised, open‐label, assessor‐blinded, 24‐week H2H trials), populations (systemic‐naïve, moderate‐to‐severe disease) and outcomes (all confirmed superiority of a first‐line biological treatment over FAE). In all trials, withdrawal rates in the FAE group were high, ranging from 22% to 55.7% 5–8 ; withdrawal rate in CHANGE was 44.8%. However, there was a difference across these trials in how FAE was titrated.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The trials all had similar designs (randomised, open‐label, assessor‐blinded, 24‐week H2H trials), populations (systemic‐naïve, moderate‐to‐severe disease) and outcomes (all confirmed superiority of a first‐line biological treatment over FAE). In all trials, withdrawal rates in the FAE group were high, ranging from 22% to 55.7% 5–8 ; withdrawal rate in CHANGE was 44.8%. However, there was a difference across these trials in how FAE was titrated.…”
Section: Discussionmentioning
confidence: 85%
“…Four recently published trials also reported H2H comparisons of FAE to a biologic for the treatment of moderate‐to‐severe psoriasis. These were secukinumab, 5 ixekizumab, 6 guselkumab 7 and risankizumab 8 . The trials all had similar designs (randomised, open‐label, assessor‐blinded, 24‐week H2H trials), populations (systemic‐naïve, moderate‐to‐severe disease) and outcomes (all confirmed superiority of a first‐line biological treatment over FAE).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are some caveats when interpreting the data. While biologics act very fast, treatment with FAE or DMF shows significant clinical effects beginning at week 12 at the earliest . Full‐dose guselkumab is given from week 0, while FAE are typically uptitrated over a period of 9 weeks (maximum dosage six tablets per day).…”
mentioning
confidence: 62%
“…In clinical studies, ixekizumab has been shown to be effective in patients with moderate-to-severe chronic plaque psoriasis, demonstrating rapid clinical improvements and a favorable safety profile when compared with placebo [2][3][4][5], and in headto-head studies versus etanercept [2], methotrexate, fumaric acid esters [6], the IL-12/23 inhibitor ustekinumab [7], or the IL-23 inhibitor guselkumab [8]. In phase 3 randomized studies, ixekizumab has been shown to be effective through 60 [9], 108 [10], 156 [11], and 204 [12] weeks of treatment.…”
Section: Introductionmentioning
confidence: 99%